Android-based Application Development on Thermochemistry using Kvisoft Flipbook Maker and Apps Geyser - Dwi Gilang Romadhon; Setia Rahmawan (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
The complexity of thermochemistry and its abstract nature is often difficult for students to study. To address this issue, we designed an Android-based application using Kvisoft FlipBook Maker and AppsGeyser to help their study process. This research focuses on improving students' understanding of thermochemistry through digital learning tools. Using the ADDIE (Analyze, Design, Develop, Implement, and Evaluate) development model, we created an interactive learning module in the form of an android application. The reason for using an android application is because there is no longer a risk that the learning module will be hidden or forgotten with other files, the application can also be accessed easily as long as it has an android device. Previous research has also indicated that a digital teaching tool can improve the understanding of chemistry learning due to attractive visualization and self-learning opportunities. This study involved validation from media and material experts, as well as assessment from chemistry teachers and students of SMA Muhammadiyah 7 Yogyakarta. The final product received high validation scores, with 97.8% from media experts, 93.3% from material experts, and 90.3% from chemistry teachers. In addition, 95.8% of students responded positively to the app. These findings suggest that the developed application is highly effective for independent student learning and can enhance engagement with thermochemistry concepts.